Behavioral responses of Imidacloprid-Dosed farmland birds to a simulated predation risk - Addy Orduna, Laura; Ortiz Santaliestra, Manuel Eloy; Mougeot, François; Bolivar Muñoz, Paula; Camarero Abella, Pablo R.; Mateo Soria, Rafael (ACS Publications, 2024)
Sublethal exposure to imidacloprid and other neonicotinoid insecticides may affect the neurological functions of birds. As such, behavior may be compromised. Here, we tested experimentally the effects of 1 and 6 mg/kg bw of imidacloprid on the antipredator behavioral responses of the red-legged partridge (Alectoris rufa) to simulated predator threats. Sixty-six partridges were challenged in groups or individually to intra- and interspecific alarm calls, to a raptor silhouette (aerial predation risk), and to a fox model (terrestrial predation risk). Antipredator behaviors were recorded as active (escape, active vigilance) and passive (passive vigilance, crouching, and freezing) responses. Latency in response to the stimuli, percentage of individuals who responded, response duration, speed of active responses, and vocalizations were measured. In experiments with partridges in the group, crouching against simulated predation risk lasted less time in birds treated with 6 mg a.i./kg bw than in control birds. In the experiments with individual partridges, passive vigilance against the intraspecific alarm lasted longer in birds treated with 6 mg a.i./kg bw than in control birds. The observed hyperreactivity to the predatory threat after a sublethal imidacloprid exposure can have consequences on survival under field conditions, where predation is a main driver of population dynamics.